Loyalty Model for Ethnic Restaurants: The Role of Quality and Value - Wahyu Rafdinal; Dwi Suhartanto (Politeknik Negeri Bandung, 2020)
Recent research discusses the need for a better understanding of customer perceptions about ethnic restaurant attributes such as qualities and values in influencing the process of customer loyalty and ethnic restaurant competitiveness. This study aims to analyze the importance of quality and value in influencing loyalty in ethnic restaurants. The sample in this study are 210 respondents who visit ethnic restaurants twice in the past month. Data are collected using questionnaire survey which was done in around Bandung Raya. The analysis technique used is the Structural Equation Model with Partial Least Square. The results showed that the quality of ethnic restaurants such as food quality and physical environment quality directly influence loyalty. Meanwhile, service quality has an indirect effect on loyalty through value. Then, price value and emotional value directly influence loyalty. This study provides a better understanding of scholars and managers in ethnic restaurants about restaurant quality, value, and loyalty. This study suggests that the quality of ethnic restaurants, such as food quality, service quality, and physical environment quality can be valuable indicators for increasing values and loyalty, as well as being an attractive marketing strategy for the preferences of different market segments for ethnic restaurant experiences.